Antiurolithiatic activity of natural constituents isolated from Aerva lanata - Basavaraj M. Dinnimath; Sunil S. Jalalpure; Umesh K. Patil (Journal of Ayurveda and Integrative Medicine, 2017)
Background: Pashanabheda is used as antiurolithiatic in Ayurveda. In the present study, Aerva lanata (L) Juss. ex. Schult (Amaranthaceae) from Western Ghats of India was selected for isolation of active constituents and screening for antiurolithiatic potentials. Objective: Screening of compounds isolated from A. lanata for antiurolithiatic potentials. Materials and methods: Ethylene glycol (0.75% v/v) induced urolithiasis model was used to study the antiurolithiatic activity in male Wistar albino rats. The animals were divided into five groups containing six each. Based on the LD50 of the plant extract (2000 mg/kg b.w) equivalent dose was calculated from their yield. Two isolated compounds (quercetin and betulin) of A. lanata were screened for antiurolithiatic potentials in calculi induced (ethylene glycol 0.75% v/v) male Wistar albino rats by administering 2 mg/kg b.w/day orally as test dose for 28 days. Results: The urine volume was found to be significantly increased from 12.76 ± 0.10 ml to 21.35 ± 0.20 ml in the rats treated by quercetin and 21.50 ± 0.21 ml in rats treated by betulin. Urine microscopy revealed significant reduction (p < 0.001) in the size of calculi and significantly enhanced (p < 0.001) excretion of calcium, oxalate, phosphate, whereas the level of magnesium was increased. SEM of kidney sections has revealed reduction in the calculi in treated animals. Serum analysis has revealed significant reduction in the level of BUN and creatinine in treated rats. Conclusion: The isolated quercetin and betulin from A. lanata have shown mild diuretic effect as well as antiurolithiatic effect by significantly reducing the size of calculi in the kidneys and enhancing the excretion of calcium, phosphate, oxalate while maintaining the level of magnesium, which is reported to be one of the calculi inhibiting factors.